The role of microbiota in the development of colorectal cancer. Issue 8 (15th January 2019) - Dai, Zhujiang; Zhang, Jingqiu; Wu, Qi; Chen, Juan; Liu, Jun; Wang, Lu; Chen, Chaowu; Xu, Jiaming; Zhang, Hongpeng; Shi, Chunfeng; Li, Zhen; Fang, Huiwen; et al.
Abstract : Colorectal cancer is the third largest cancer in worldwide and has been proven to be closely related to the intestinal microbiota. Many reports and clinical studies have shown that intestinal microbial behavior may lead to pathological changes in the host intestines. The changes can be divided into epigenetic changes and carcinogenic changes at the gene level, which ultimately promote the production and development of colorectal cancer. This article reviews the pathways of microbial signaling in the intestinal epithelial barrier, the role of microbiota in inflammatory colorectal tumors, and typical microbial carcinogenesis. Finally, by gaining a deeper understanding of the intestinal microbiota, we hope to achieve the goal of treating colorectal cancer using current microbiota technologies, such as fecal microbiological transplantation.